From Mexico to Ireland: Cultural Identity Identified in Dublin’s Mexican-themed Restaurants - Rodriguez, Ariana Izzabela (Trinity College Dublin, School of Languages, Literatures, and Cultural Studies, 2025)
In 2010, the United Nations Educational, Scientific and Cultural Organisation (UNESCO) titled Mexican food an intangible cultural heritage of humanity. Cultural heritage is generally understood as a country's tangible and intangible ancestral assets, such as monuments, traditions, and rituals (Bortolotto 2006). For UNESCO Mexican ambassador Andres Morales, the cultural heritage of a country is simply the ‘the spirit of people: the most intimate connection that people in a community establish with each other, with their origins, and with their territory’ (UNESCO 2023). While cultural heritage preserves these elements, cultural identity involves how these elements shape individuals' or groups' sense of belonging. Grimson (2010) argues that culture and identity should be viewed as separate entities, whereas Clarke (2008) believes they are intertwined, with culture being a learned part of identity. Hall (1990) describes cultural identity as a continuous process of becoming and belonging within social structures. Mraz (2009) applies this to Mexican culture, noting its dynamic construction, deconstruct, and reconstruction through visual representation. Hall’s (1990) and Mraz’s (2009) varied discussions highlight that media often shapes stereotypes about minority groups to fit mainstream ideologies. Globalisation in media influences these stereotypes, which can either celebrate cultural diversity or reinforce harmful tropes for sociopolitical reasons (Bouymaj and De Freitas Barbosa Pereira 2022: Hall 1997: Jensen, Arnett, and McKenzie 2011). Therefore, the communication of Mexico’s cultural identity is closely linked to media globalisation. For Maddicks (2005), Pilcher (2012), and Zoucha and Zamarripa-Zoucha 2020), the symbol-laden essence of Mexican food serves as a central mode in the communication of Mexican cultural identity, or Mexicanidad. Parasecoli (2014) states that the communicated images and texts of Mexico’s culturally salient food and drink items, such as Mexican tequila, have become modified and negotiated due to globalisation to create an experience for consumers rather than for those with Mexican heritage. This process of reconstructing Mexicanidad for a broad audience has begun to enter scholarly discussions today as many argue that such visual and textual conveyances affect the survival of this intangible cultural heritage.